[March leaders approaching Dexter lawn?] (1995)
Three Black people in suits are walking towards Dexter lawn. They are probably (based on related photographs in this collection) leading a march. In the foreground, on the lawn, one White student is writing into a notepad, they are wearing a black suit and tie. There are three other students standing next to the White student.